2019
DOI: 10.3390/gels5010012
|View full text |Cite
|
Sign up to set email alerts
|

Porous Starch Materials via Supercritical- and Freeze-Drying

Abstract: The production of porous materials based on starch has been explored with supercritical drying—yielding aerogel—and freeze-drying. The two drying procedures were applied on the same gelling solution of amylomaize starch pasted at 140 °C and for two concentrations (5 and 10 wt.%). After gelation and retrogradation, water from the samples to be supercritically dried was exchanged to ethanol. The resulting starch aerogel presented high specific surface area (197 m2/g). Freeze-drying was assessed by investigating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 47 publications
9
40
0
Order By: Relevance
“…These fibrils are composed of amylose crystal presenting a characteristic B-type Xray diffraction pattern corresponding to their double helix structure. Garcia-Gonzalez et al observed the same characteristic Xray diffraction pattern for starch aerogel [19] along with our results indicating a similar fibril structure in starch aerogel SEM pictures [36]. Lu et al studied the retrogradation of potato amylose at different temperatures and showed that after 24 h, only 13% of amylose retrograded at 25°C compared with 60% at 5°C [37].…”
Section: Retrogradation and Solvent Exchangesupporting
confidence: 86%
“…These fibrils are composed of amylose crystal presenting a characteristic B-type Xray diffraction pattern corresponding to their double helix structure. Garcia-Gonzalez et al observed the same characteristic Xray diffraction pattern for starch aerogel [19] along with our results indicating a similar fibril structure in starch aerogel SEM pictures [36]. Lu et al studied the retrogradation of potato amylose at different temperatures and showed that after 24 h, only 13% of amylose retrograded at 25°C compared with 60% at 5°C [37].…”
Section: Retrogradation and Solvent Exchangesupporting
confidence: 86%
“…This important biopolymer is largely applied as thickening and gelling agent in food and non-food products [ 1 , 2 ]. Moreover, owing to its biodegradability and biocompatibility, starch has been widely associated with the development of new versatile eco-friendly porous materials, in particular, aerogels [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starch-derived aerogels, low-density mesoporous solids with high specific surface area, are commonly prepared in three steps: hydrogel formation, solvent exchange using ethanol, and supercritical drying with carbon dioxide (CO 2 ) [ 3 , 7 ]. Aerogel properties are highly dependent on the source of starch and its concentration, degree of gelatinization, and retrogradation [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, the impact of gel formation parameters on mechanical and physical properties were investigated. Bauldron and colleagues investigated the difference between freeze-drying and supercritical drying on the physical properties of amylomaize starch gels [4]. It was determined that freeze-drying resulted in macroporous gels with 20-100 µm pores, whereas supercritical drying led to gels with 1 µm pores.…”
mentioning
confidence: 99%